DNA-based species identification of ancient salmonid remains provides new insight into pre-contact Coast Salish salmon fisheries in Burrard Inlet, British Columbia, Canada. (June 2021) - Morin, Jesse; Zhang, Hua; Royle, Thomas C.A.; Speller, Camilla; Alcaide, Miguel; Morin, Ryan; Yang, Dongya
Highlights: aDNA analysis is used to identify the species of salmonids harvested in pre-contact times. Chum salmon are found to dominate all assemblages during all periods. Other salmonids were harvested at much lower frequencies. Sampled settlements were likely occupied during fall-winter and perhaps spring. Abstract: This study uses ancient DNA analysis to identify the species of salmonids from a number of pre-contact Coast Salish settlements in Burrard Inlet, Canada dating from about 390 BCE to CE 1600. Our results indicate that chum salmon ( Oncorhynchus keta ) dominates all Burrard Inlet zooarchaeological assemblages through time, followed distantly by pink salmon ( Oncorhynchus gorbuscha ), sockeye ( Oncorhynchus nerka ), coho ( Oncorhynchus kisutch ), and Chinook ( Oncorhynchus tshawytscha ), indicative of very stable local fisheries. These results indicate that the four well-sampled sites appear to have been occupied during the fall and winter and perhaps during the spring.